Subseasonal Reversal of Winter Temperature Over Northeast China in 2014/2015: Role of Arctic Sea Ice - Dai, Haixia; Fan, Ke (Frontiers in Environmental Science, 2022)
This study investigates the temperature reversal over Northeast China (NEC) in winter 2014/2015, focusing on the variations of related general circulations and the affecting mechanisms of the Arctic sea ice on daily scale. It turns out to be the coupled impacts of the eastward propagations of tropospheric wave trains from the North Atlantic Ocean and the downward reflections of planetary wavenumber-1 from the stratosphere that resulted in the subseasonal reversal of winter temperature over NEC in winter 2014/2015. Also, such anomalous atmospheric circulations can be attributed to sea-ice anomalies over the Davis Strait–Baffin Bay (SIC-DSBB) and the Barents–Kara Sea (SIC-BKS) in November 2014. SIC-DSBB anomalies in November 2014 excited the eastward propagation of Rossby waves via the tripole pattern of sea surface temperature over the North Atlantic Sea, leading to the colder condition over NEC in the first and middle ten days of December 2014. Anomalously heavy SIC-BKS also triggered wave trains from the polar region to Eurasia, strengthening the Rossby wave induced by SIC-DSBB. Moreover, the wave trains suppressed the upward propagation of planetary wavenumber-1 over the Siberia region, strengthening the stratospheric polar vortex. However, the sea-ice anomalies over these two domains only existed in November 2014. Thus, the tropospheric mechanisms by which the Arctic sea ice affected the temperature over NEC only lasted to late December 2014. Meanwhile, the stratospheric anomalies propagated downwards with the planetary wavenumber-1, favoring the positive phase of Arctic Oscillation in the troposphere and the warm condition over NEC since the last week of December 2014. Consequently, the temperature over NEC reversed in winter 2014/2015.